PENGARUH PROMOSI, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE: (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Katolik Santo Thomas Medan) - Melina, Serli; Saragih, Nawary (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The purpose of this study was to find out and explain the effect of promotion, product quality and price on purchasing decisions on the Shopee marketplace (Case Study of Students of the Faculty of Economics and Business, Catholic University of Santo Thomas Medan). Data collection was carried out by distributing questionnaires to 100 students who made purchases on the Shopee marketplace. Testing techniques used in research are validity testing, reliability testing, multiple linear regression analysis, hypothesis testing (F test and t test) and analysis of the coefficient of determination. Data analysis in this study used SPSS version 25. Simultaneously (F test) shows promotion, product quality and price have a positive and significant effect on purchasing decisions on the Shopee marketplace. Partially (t test) shows that promotion has a positive and significant effect on purchasing decisions on the Shopee marketplace. Product quality has a positive and significant effect on purchasing decisions on the Shopee marketplace. Price has a positive and significant effect on purchasing decisions on the Shopee marketplace. The coefficient of determination (R2) is 0.549, meaning that the purchase decision can be explained by promotion, product quality and price by 54.9%, while 45.1% is explained by other factors not explained in this study.